2010
DOI: 10.3171/2009.9.jns0997
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh-dose intraarterial infusion of verapamil through an indwelling microcatheter for medically refractory severe vasospasm: initial experience

Abstract: Prolonged intraarterial infusion of verapamil is a safe and effective treatment for medically refractory severe vasospasm and reduces the need for angioplasty in such cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
38
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 49 publications
1
38
0
4
Order By: Relevance
“…It has been suggested by others that distal vessels are more affected by medication infusion than proximal vessels. 7,10 In this study, the effects of intra-arterial verapamil were not different between proximal and distal arterial segments. As shown in Fig 1, intra-arterial vasodilator infusion has the benefit of simultaneous treatment of an entire arterial distribution, including distal vessels not accessible by angioplasty.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…It has been suggested by others that distal vessels are more affected by medication infusion than proximal vessels. 7,10 In this study, the effects of intra-arterial verapamil were not different between proximal and distal arterial segments. As shown in Fig 1, intra-arterial vasodilator infusion has the benefit of simultaneous treatment of an entire arterial distribution, including distal vessels not accessible by angioplasty.…”
Section: Discussionmentioning
confidence: 65%
“…Other studies have reported changes in gross neurologic status in treated patients. [7][8][9][10]17 Those parameters were outside the scope of the current study. In the absence of a control patient population, those data may be of limited value.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…36 Verapamil is an L-type calcium-channel blocker (CCB) currently used clinically for intra-arterial administration in the treatment of cerebral vasospasm with minimal adverse effects. [37][38][39] Previous studies also support a possible therapeutic role for CCBs in stroke neuroprotection. 15,16 Flunarizine, another calcium channel blocker, showed promise in early animal data and clinical application, but failed in the double-blind Flunarizine in Stroke Trial (FIST) of 331 subjects to show clinical benefit; however, mean time interval to treatment was 13.5 h, and subjects did not undergo thrombolysis as part of the protocol.…”
Section: Discussionmentioning
confidence: 99%